Cross-sectional Study of EMG and EMG Rise During Fast and Slow Hamstring Exercises - Kasper Krommes; Markus Due Jakobsen; Thomas Bandholm; Lars Louis Andersen; Mette Zebis; Anthony Shield; Per Hölmich; Kristian Thorborg (International Journal of Sports Physical Therapy)
# Background